Fuzzy adaptive fault-tolerant control for non-identifiable multi-agent systems under switching topology - Zhang, Ao (2022)
This paper considers the leader-following consensus problem for linear multi-agent systems (MASs) with actuator faults, matched unknown nonlinearity and non-identifiable uncertainty under switching network topology for studying. A novel distributed switching fault-tolerant controller is established by approximating the nonlinear dynamics using a fuzzy logic system and by developing adaptive update laws with switching mechanisms. Besides, by introducing an adaptive mechanism to estimate the norm of weight vectors in the FLS, the developed controller can not only reduce the number of adaptive parameters but also is effective to compensate for unknown nonlinearity under the influence of actuator faults. Furthermore, it can be shown that the consensus errors are uniformly ultimately bounded by utilizing the proposed method. Compared with the existing MASs’ results with switching network topology, the nonlinearity considered is completely unknown and fewer adaptive parameters are used to counteract the influence of nonlinearity. Finally, the efficiency and effectiveness of the developed approach are demonstrated by an illustrative example.